Morphometry of Knee Menisci - Muthusamy, Sivasakthi; Sontakke, Yogesh Ashok; K., Aravindhan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2019)
Menisci is one of the most important structures of the knee joint. Owing to its importance in load sharing, shock absorption, joint stability, overall protection of articular cartilage various studies has been done on the morphometry of knee menisci by different researchers.  Different parameters have been studied such as length of outer circumference of both menisci, difference between anterior horn and posterior horn of menisci, thickness and width of menisci. Such parameters have been reviewed in this article. It gives out a wider knowledge about the morphometric parameters of knee menisci and may guide the surgeon for the new treatment modalities in case of meniscal injuries.